Sentiments of Public Opinion - Gudankwar, Aniket; Pratik Milind Mendhe,; Lukesh Namdeo Oghare,; Atharva Ramu Yemde, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Sentiment analysis, also known as opinion mining, is a computational technique that aims to identify and extract subjective information from text data, allowing us to understand and categorize the underlying sentiment expressed by individuals. With the exponential growth of social media, online reviews, and user generated content, sentiment analysis has gained significant attention as a valuable tool for businesses, researchers, and decision-makers to gain insights into public opinion, customers satisfaction, and market trends. The project is about searching the web for public opinion about people, movies, places, companies or any entities. The user of this software can type in a query that is any entity and the system mines the web for public opinion about that entity and generates a sentiment score. A positive score represents a positive public sentiment about that entity and negative score represents a negative sentiment or opinion.
Keywords: Sentiment Analysis; Opinion Mining; Computational Linguistics; Machine Learning; Deep Learning; Social Media Analysis